On the use of the South-American neutron monitors - Cordaro, E.G.; Storini, M. (Societa italiana di fisica, 2001)
Cosmic ray scientific community deserves special attention to the Chacaltaya site for its over 5 km altitude. In this site, a neutron monitor of the IGY type operated from 1960 to 1969, and the one of the NM-64 type since 1966 (16.31◦ S, 291.85◦E, height: about 5200 m a.s.l.). We discuss the relevance of such kind of detector when it is integrated with the other South-American neutron monitors: a) LARC (62.20◦S, 301.04◦E, height: 40 m a.s.l., King George Island, Antarctica; operating since 1991); b) LOS CERRILLOS (33.45◦S, 289.40◦E, height: 570 m a.s.l., Santiago, Chile; to be installed in the near future); c) HUANCAYO (12.03◦S, 284.67◦E, height: 3400 m a.s.l., Huancayo, Peru; hoping to recover its acquired data).